Prevalence and Patterns of Self-Medication Practices In Urban Field Practice Area, Dharwad - Arpitha VS; Pushpa S patil (Medsci Publications, 2022)
Background: The estimated prevalence of self-medication practices globally and nationally are 95% and 71% respectively. Inappropriate self-medication leads to irrational use of drugs and development of drug resistance. Hence, the present study was conducted to estimate the prevalence and patterns of self-medication practices in urban field practice area, SDMCMS&H, Dharwad. Methods: A cross-sectional study was conducted during 2018-2019 among adult aged 18-60 years. The estimated sample size was 335. Systematic random sampling technique was used to select the samples. Data was collected by administering questionnaire to the consented study participants. Results: A total of 335 adults participated in our study. The prevalence of self-medication practices was 46%.  Minor-illness 89(57.7%) and quick relief 50(32.46%) were the major reasons given for practicing self-medication. Fever and headache 146(94.8%) was the most common symptom and analgesic 128(83.11%) was the most common drug used. significant association was found between self-medication practices and religion, age, employment and presence of health care workers in the family. Conclusion: Around half of the study participants practiced self-medication. Easy availability and limited knowledge are the reasons for wide range of practice. Creating awareness about dangers of self-medication is important to prevent untoward effects and drug resistance.